Greece : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper analyzes the growth prospects of the Greek economy. It is estimated that exceptional factors boosted growth by 1 percentage point per year in recent years and, under current trends and policies, growth is likely to drop to about 3 percent by the end of the decade. The paper places the recent strong growth performance of the Greek economy in a historical and international context. It also assesses the impact of exceptional factors on growth, and presents statistical estimates of potential growth.